Improving Family Function in Modifying a Healthy Home Environment - Rosidin, Udin; Shalahuddin, Iwan; Yamin, Ahmad; Lukman, Mamat; Pristasari, Sheizi (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
A healthy community is a group where residents play an active role in overcoming public health problems independently. Efforts that can be made to improve community health must start with family health. Based on the results of a survey that has been conducted, most families in RW 06, Sukamentri Village, Garut City District, showed that they did not understand the function of the family in the health sector, especially efforts to modify the home environment to meet health requirements. Data shows waste disposal habits, as many as 59.56% use open trash bins. In waste management, the majority (79.78%) do not sort waste. Ventilation data shows that most houses (61.80%) have adequate ventilation. These data show that some families have not been able to maintain the health of their home environment properly, such as waste disposal, wastewater disposal, ventilation, and other environmental health problems. Considering these problems, interventions need to be carried out to overcome the problem of low implementation of family functions in modifying the home environment to meet health requirements. The purpose of the activity is to increase family knowledge in implementing family functions in the health sector. The stages of the activity start from identifying problems, social preparation, and administrative preparation. Then activity results with the implementation and evaluation stages of the activity. The results of the activity showed an increase in family knowledge by 27.1 points. The average pretest score was 52.3 points and the average posttest score was 79.4 points. The activity went smoothly according to the planned time. It is hoped that the activities that have been implemented can be continued periodically by the Guntur Health Center.